Fifty years of tagging skates (Rajidae): using mark-recapture data to evaluate stock units. (22nd February 2020) - Bird, C.; Burt, G. J.; Hampton, N.; McCully Phillips, S. R.; Ellis, J. R.
Abstract: Despite increased focus on ascertaining the status of elasmobranch fish, the stock units for many species are uncertain. Data from mark-recapture tagging studies undertaken from 1959–2017 were analysed for 13 batoid species. Data were most comprehensive for skates (Rajidae), with 22, 374 released and 3342 (14.9%) returned. Most data related to thornback ray Raja clavata, blonde ray R. brachyura and spotted ray R. montagui . Tags were generally returned from areas less than 50 km from their release, and usually from the ICES Division in which they were released. However, straight-line distances travelled of up to 910 km ( R. brachyura ) and 772 km ( R. clavata ) were recorded, highlighting that individual skates are capable of longer-distance movements. The maximum time at liberty was 16.6 years ( R. clavata ). Whilst mark-recapture data indicated that the current stock units used by ICES are broadly appropriate, southward movements of several skate species tagged off Northern Ireland (Division 6.a) to the Irish Sea (Division 7.a) were observed. In contrast, skates tagged in the Irish Sea and Bristol Channel (Division 7.f) generally remained in that area, with only occasional recaptures from Division 6.a.